"Estación de transferencia intermodal El Silencio" Plan parcial tejidos vitales Barrancabermeja - Santander (2017)
The partial plan of vital tissues is implanted as a model of a city made and designed for people, avoiding the social and environmental impact that entails such an important development, including in the environmental factors within the proposal and creating a physical relationship between Existing and proposed. This proposal consists of development plans in housing, services, tourism, education, infrastructure and industry, vocational issues that occur on the site but do not comply with infrastructure and optimal planning and that in the partial plan vital tissues will have a Place planned and built for an optimal and integral operation of each of these activities.